Fuzzy Smokers Growth Model - Herlinda Nurafwa Sofhya (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
The tobacco epidemic is one of the biggest public health problems in the world. Based on the data from WHO, Tobacco kills nearly 6 million people a year around the world. Monitoring tracks of smokers' growth population can be important things for the government to find the best implement policies to overcome this problem. This paper presents a smoker's growth model with uncertainty in the transmission and recovery rate. In classical smoker's growth model, the transmission and recovery rate assumed to be constant. However, in reality, the age of the population is heterogeneous, and the transmission among the population may depend on the age of the smoker. Therefore, in this paper, the transmission and recovery rate of smokers' growth model depends on the age of smokers. We divide the transmission and recovery rate into three categories based on age: Children (0-10), Adolescent (10-30), Adult (30-60). The uncertainty of transmission and recovery rate in this model represented by a triangular fuzzy number. The most important things in the model are the basic reproduction number. A basic reproduction number is an indicator of when the endemic case will occur. Therefore, the main focus of this paper is to determine the basic reproduction number of fuzzy smokers growth models using the fuzzy expected value concept. The result is the basic reproduction number of the fuzzy model is an interval. This may can be used as an upper and lower limit of the basic reproduction numberÂ Â